2014
DOI: 10.1021/sc400342x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Urea Bioelectrochemical System for Wastewater Treatment Processes

Abstract: Due to the high cost of delivering supplies to space, the recovery of potable water from spacecraft wastewater is critical for life support of crewmembers in short-and long-term missions. It is estimated that in future long-term space missions, human wastes such as urine will contribute more than 50% of the total waste. Thus, we will demonstrate how unused components, such as urea, can be recovered and reused in wastewater recycling processes. In this system, a urea bioreactor (GAC-urease) converts urea to amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The batch system results serve as a reference for the continuous system. A research conducted by [22] shows that only slight differences were observed with a change in pH in the immobilization of urease. In another research conducted by Nelson and Cox [23], the effect of pH values results on the variations of enzymatic activity and alteration in charges of the protein and substrates in the reaction were investigated.…”
Section: Effect Of Feed Concentration Ph On Urease Activitymentioning
confidence: 99%
“…The batch system results serve as a reference for the continuous system. A research conducted by [22] shows that only slight differences were observed with a change in pH in the immobilization of urease. In another research conducted by Nelson and Cox [23], the effect of pH values results on the variations of enzymatic activity and alteration in charges of the protein and substrates in the reaction were investigated.…”
Section: Effect Of Feed Concentration Ph On Urease Activitymentioning
confidence: 99%
“…In fact, the ease of storage of ammonia in comparison to hydrogen [36] makes it suitable to be used as an alternative fuel because of its high energy density (12.6 MJ L −1 ), especially for space stations. The idea to achieve resource recovery from water recycling systems was already developed as a proof of concept by Nicolau et al [37] who based their recycling system on the use of a bioreactor that was able to produce a high amount of ammonia, which was used to feed an electrochemical cell in order to generate electrical energy. However, it is well known that processes based on biological treatment in some special fields, such as space stations, are not safe [6,38,39].…”
Section: Influence Of Visible Light Modulation Techniques On Urea Phomentioning
confidence: 99%
“…The proposed system was developed to serve as a urea biosensor. Urea bio-electro-oxidation was also considered as a possible method for the treatment of urine at space stations [115]. In the first step, urea is converted to ammonia in a bioreactor based on urease.…”
Section: Bio-electro-oxidation Of Ureamentioning
confidence: 99%